2011
DOI: 10.1144/m36.46
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 46 The Serra Azul Formation, Paraguay Belt, Brazil

Abstract: A new succession of diamictites and siltstones has been found within the Araras Group and is interpreted to record Ediacaran glaciation in the northern Paraguay Belt, Brazil. This discontinuous stratigraphic unit, named the Serra Azul Formation (Fm.) (Figueiredo et al. 2005;Alvarenga et al. 2007), is up to 300 m thick. It lies above dolomites of the Nobres Fm. and below sandstones of the Raizama Fm. At the stratotype section, the Serra Azul Fm. comprises c. 70 m of massive glacial diamictites, overlain by 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Figueiredo et al . () suggested that the diamictite is not observed in the west due to non‐deposition or erosion after deposition. Erosion is not considered to be a likely possibility, given that accommodation space is generally considered to increase in the wake of glaciation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figueiredo et al . () suggested that the diamictite is not observed in the west due to non‐deposition or erosion after deposition. Erosion is not considered to be a likely possibility, given that accommodation space is generally considered to increase in the wake of glaciation.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent contribution, Figueiredo et al . () stated that the Serra Azul Formation is between 250 m and 300 m thick in the region where it is completely exposed; however, the base of the Serra Azul Formation was not documented. McGee et al .…”
Section: Measured Sectionsmentioning
confidence: 99%
“…1.4, Table 1.4). The Araras Group in the northern Paraguay Belt, in particular, has been the subject of interdisciplinary studies and preserves some of the best evidence for Ediacaran glaciation in South America (Figueiredo et al 2011). New entries to the South American database include the sections in Peru, Uruguay and Argentina as well as the Moema laminites in Brazil.…”
Section: South Americamentioning
confidence: 99%